Influence store atmosphere and word of mouth on the purchase decision mediated buying interest (Studies on Aneka Jaya Consumers) - Cicik Harini; SB Handayani; Sauca Ananda Pranidana; Heru Sri Wulan; Leonardo Budi H (Institute of Computer Science (IOCS), 2023)
This research aimed to examine the effect of store atmosphere and word of mouth on the buying decision which is mediated by buying interest. The research was quantitative research and makes use of quantitative data sorts, namely information measured on a numerical scale. The population is the number of customers of Aneka Jaya that's divided into three branches in Semarang. The records series technique uses nonprobability sampling and the wide variety of samples is a hundred respondents. In addition, the facts evaluation method makes use of route evaluation. The results of the examine concluded that Store Atmosphere had a tremendous and huge impact on buy goal, Word of Mouth had a superb and full-size effect on buy purpose, Store Atmosphere and Word of Mouth simultaneously had a tremendous and giant impact on purchase purpose, buy goal had a positive and widespread effect on buying choices , Store Atmosphere has a fantastic and widespread impact on shopping selections, Word of Mouth has a nice and vast effect on shopping selections, shopping for hobby has a superb and large effect mediating Store Atmosphere on buying selections, and buying interest has a superb and full-size impact mediating Word of Mouth on buying choices on Aneka Jaya clients unfold over 3 branches.